Manure sheds and milk production : encouraging results in Senegal - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Raising cattle in cowsheds is proving to be a great success in the cotton growing zone of Senegal. The local textile fibre development company (Sodefitex) is encouraging this type of intensive livestock husbandry as one way the area can better face...